Pesquisa de marketing para a inserção de novos produtos: um estudo de caso numa distribuidora de frutas em Marabá - PA. - Pizza, Mario Otávio Morales (Universidade Federal do Tocantins, 2020)
This study was carried out based on a marketing research at the company Orange Gomes, located in the city of Marabá-PA. In the market since 2012 and currently is the main supplier of oranges in the south of Pará. In this sense, this article had as general objective, to analyze the market viability for the insertion of new products in this distributor. Likewise, it proposes to identify the potential local market and the most preferred fruits and vegetables of the customers in the local market. Thus, this research promoted the elaboration of a single and specific study and in this way generated a case study. As methodological procedures, a bibliographic research was carried out in books, articles, websites and magazines, and the field research was carried out, which was developed through the application of a questionnaire to ascertain the satisfaction and interest of the clients of the Company for insertion of new products. It also had a qualitative-quantitative. Such procedures made it possible to identify that most of the customers are willing to work with new products in the future marketed by the company Orange Gomes. In addition, it has been noticed that there is considerable demand for new products among the company's customers.